E-Participation and ISO 37120 as a Reference for the Implementation of Sustainable Development in a Smart City - Legutko-Kobus, Paulina (Studia Ecologiae et Bioethicae, 2021)
Smart cities approach and handle public matters, using information and communication technologies (ICT). Since the concept surfaced in the 1990s, a smart city has been regarded as one seeking to embody the principle of sustainable development. The article focuses on the following research questions: How are smart cities defined and classified? Which Polish cities have made it to the global smart city rankings? How can the smart city concept contribute to the implementation of sustainable development? Polish cities are not ranked among the smart city leaders, globally. However, many of them put some elements of the Smart City 3.0 concept into use, thus, applying the “smart” ideas for sustainable development implementation. The smart city dimensions (up to six are named in the publications on the subject) refer to some aspects of sustainable development, while allowing the achievement of integrated governance. On one hand, the ISO 37120 standard is a certificate of implementation of the smart concept; but, on the other hand, it is used as a reference for assessment of the level of sustainable development implementation. Polish cities certified, according to this standard, are: Gdynia, Gdańsk, Kielce, Lublin, and Warsaw. The article highlights that the implementation of the smart city concept is very likely to contribute to the faster and more effective achievement of sustainable development in urban areas. This can be done, not only through a greater use of high-end technologies but, above all, through civic involvement (by employing e-participation tools for co-determination purposes) and cities’ aspirations to collect and share better quality and more accurate data, on various aspects of sustainable development.